2001
DOI: 10.1021/bi011177o
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Essential Histidines in Human Pituitary Glutaminyl Cyclase

Abstract: Glutaminyl cyclase (QC, EC 2.3.2.5) catalyzes the formation of the pyroglutamyl residue present at the amino terminus of numerous secretory peptides and proteins. Treatment with diethyl pyrocarbonate inactivated recombinant human QC with the apparent modification of three essential histidine residues. Comparisons of the protein sequences of QC from a variety of eukaryotic species show four completely conserved histidine residues. Mutation of each of these residues to glutamine resulted in two mutant enzymes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 26 publications
4
43
1
Order By: Relevance
“…1C), suggesting some roles in catalysis. Mutations of those amino acids decreased enzyme activity significantly (Table 1), in agreement with some results by Bateman et al (32). Interestingly, the acidic E201, D248, and D305 are pointing to each other at pH 6.5 and 8.0, likely forming hydrogen bonds between them.…”
Section: Resultssupporting
confidence: 90%
“…1C), suggesting some roles in catalysis. Mutations of those amino acids decreased enzyme activity significantly (Table 1), in agreement with some results by Bateman et al (32). Interestingly, the acidic E201, D248, and D305 are pointing to each other at pH 6.5 and 8.0, likely forming hydrogen bonds between them.…”
Section: Resultssupporting
confidence: 90%
“…5), the binding motif His-Asp-Glu-Asp-His of the two Zn 2ϩ ions present in this clan of hydrolases is also conserved in human QC. Furthermore, as shown in another study (9), modification of two of the identified histidine residues, His-140 and His-330, which are probably necessary for metal binding (Fig. 5), leads to a complete loss of catalytic activity.…”
Section: Figsupporting
confidence: 66%
“…Because of the complete reactivation by the addition of Zn 2ϩ ions to apo QC, one can conclude that human and probably all mammalian QCs are Zn 2ϩ -dependent. Recently, a relationship of the tertiary structure of human QC and the aminopeptidase from Vibrio proteolyticus, a prominent member of the clan MH family M28 of metallopeptidases, was proposed (9). Comparing the sequence of human QC with those of two members of the clan MH (Fig.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations